Optimal iterative learning control of linear uncertain systems : a linear matrix inequality approach - Liu, Wen. (2008)
The objective of this paper is to develop a new approach for designing Iterative Learning Control (ILC) with repetitive linear time-varying uncertain system. Contributions of this methodology light up and expand the creative idea of Linear Matrix Inequalities (LMIs) applications.